2015
DOI: 10.4236/jssm.2015.83040
|View full text |Cite
|
Sign up to set email alerts
|

Business Process Reengineering in Government Agencies: Lessons from an Experience in Mexico

Abstract: This paper is based on the findings from two research projects in the Mexican port subsector and shows evidence that business process reengineering is a viable tool for government reform in Latin America. The paper opens with a brief description of New Public Management (NPM), a model used in recent efforts for state reform in the region of Latin America. The modernization of Mexican ports is based on the NPM paradigm. The following section includes a definition of business process reengineering, its methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The performance problem as experienced in APSOs can be adequately addressed through the adaptation to process reengineering (PR) and a clear understanding of its CSFs which were discussed in the preceding part of this paper. Finally, the pragmatists think that although PR is applicable in APSO, there is need for a customized methodology owing to the unique characteristics of APSOs and lessons should be adapted rather than adopted from the private sector, together with keen attention to basic success and failure factors (Fragoso, 2015). The pragmatists also recognize several regulatory, statutory, and legal issues that affect swift PR ISSN 2161-7104 2020 principle application in APSOs and the need for major stakeholders to lend their weights on every proposed idea before acceptance, adoption, and application.…”
Section: Methodology For Pr Application In Apsos and Lessons From Thementioning
confidence: 99%
“…The performance problem as experienced in APSOs can be adequately addressed through the adaptation to process reengineering (PR) and a clear understanding of its CSFs which were discussed in the preceding part of this paper. Finally, the pragmatists think that although PR is applicable in APSO, there is need for a customized methodology owing to the unique characteristics of APSOs and lessons should be adapted rather than adopted from the private sector, together with keen attention to basic success and failure factors (Fragoso, 2015). The pragmatists also recognize several regulatory, statutory, and legal issues that affect swift PR ISSN 2161-7104 2020 principle application in APSOs and the need for major stakeholders to lend their weights on every proposed idea before acceptance, adoption, and application.…”
Section: Methodology For Pr Application In Apsos and Lessons From Thementioning
confidence: 99%
“…Sometimes, cost reduction can be analyzed in terms of simply eliminating an activity step (a link in a chain or a modular element) in an existing service, as this kind of cost reduction is often the easiest to measure and quantify. More frequently, however, it means reconfiguring the current activity steps in a lower cost manner: that is, some kind of "business process reengineering" (BPR) [167] applied to public agencies [147,[168][169][170][171]. The introduction of electronic communication systems (for example, the use of email) facilitates many such BPR cost reductions, with each individual reconfiguration sometimes having only an almost imperceptible impact on aggregate production cost.…”
Section: Estimating Value Creation: Either Currently or Under Potentimentioning
confidence: 99%
“…Fragoso [15] presented a study on the findings from the implementation of BPR in two Mexican ports. The study confirmed that BPR is a good technique to be used in improving the management of public agencies.…”
Section: Related Workmentioning
confidence: 99%